Inhibition of PI3Kinase-α is pro-arrhythmic and associated with enhanced late Na+ current, contractility, and Ca2+ release in murine hearts. (July 2019) - Zhabyeyev, Pavel; McLean, Brent; Chen, Xueyi; Vanhaesebroeck, Bart; Oudit, Gavin Y.
Abstract: Background: Phosphoinositide 3-kinase α (PI3Kα) is a proto-oncogene with high activity in the heart. BYL719 (BYL) is a PI3Kα-selective small molecule inhibitor and a prospective drug for advanced solid tumors. We investigated whether acute pharmacological inhibition of PI3Kα has pro-arrhythmic effects. Methods & Results: In isolated wild-type (WT) cardiomyocytes, pharmacological inhibition of PI3Kα (BYL719) increased contractility by 28%, Ca 2+ release by 20%, and prolonged action potential (AP) repolarization by 10–15%. These effects of BYL719 were abolished by inhibition of reverse-mode Na + /Ca 2+ exchanger (NCX) (KB-R7943) or by inhibition of late Na + current (INa-L ) (ranolazine). BYL719 had no effect on PI3Kα-deficient cardiomyocytes, suggesting BYL719 effects were PI3Kα-dependent and mediated via NCX and INa-L . INa-L was suppressed by activation of PI3Kα, application of exogenous intracellular PIP3, or ranolazine. Investigation of AP and Ca 2+ release in whole heart preparations using epicardial optical mapping showed that inhibition of PI3Kα similarly led to prolongation of AP and enhancement of Ca 2+ release. In hearts of PI3Kα-deficient mice, β-adrenergic stimulation in the presence of high Ca 2+ concentrations and 12-Hz burst pacing led to delayed afterdepolarizations and ventricular fibrillation. In vivo, administration of BYL719 prolonged QT interval [QTcF (Fridericia) increased by 15%] in WT, but not in PI3Kα-deficient mice. Conclusions: Pharmacological inhibition of PI3Kα is arrhythmogenic due to activation of INa-L leading to increased sarcoplasmic reticulum Ca 2+ load and prolonged QT interval. Therefore, monitoring of cardiac electrical activity in patients receiving PI3K inhibitors may provide further insights into the arrhythmogenic potential of PI3Ka inhibition. Graphical abstract: Unlabelled Image Highlights: Inhibition of PI3Kα is arrhythmogenic. Activation of late Na + current is associated with QTc prolongation. PI3Kα-dependent Ca 2+ overload exacerbates β-adrenergic triggered arrhythmias. Ranolazine inhibits late Na + current and normalizes Ca 2+ load.